Resource Utilization and Profitability of Rice Production in The Terai Region of Nepal: Rice Production Profitability in Nepal's Terai - Sherestha , Lal Kumar; Thapa, Yam Bahadur; Dhakal, Shiva Chandra; Gauchan, Devendra (SAARC Journal of Agriculture, 2025)
Rice is the most important staple food crops in Nepal; however, the national yield of rice is low which has led in insufficient supply and heavy annual import. So, this study assessed the profitability and resource utilization of main and spring season rice production. A Semi-structured interview schedule was administered in 2022 among 360 randomly selected main-season rice-producing farmers across three major rice-producing districts of the Terai region of Nepal. Similarly, it conducted four Focus Group Discussions (FGDs) to collect necessary data for spring season rice from two Terai districts within similar agro-ecological regions. Cobb-Douglas production function was used to assess the resource utilization in main season rice production. The result revealed that the total cost and revenue of spring season rice production per hectare was higher, with a benefit-cost ratio of 1.63 compared to the main season. It was found that major resources such as the cost of seed, farm yard manure (FYM), chemical fertilizer, micronutrients, and pesticides were underused. On the other hand, the cost of labor, tillage, and harvesting were found to be overused in the main season of rice production. The proportion of the increase in rice income to the increase in costs of inputs for main season rice production was less, as indicated by the return to scale being less than unity. Hence, the study recommends to focus on addressing on prioritization to increase the cropping area under spring season rice and optimization in the use of resources supported by improved technologies to improve profitability and increase farmers’ income from rice this can eases the constraints in the domestic supply of rice and thereby contribute to lowering the annual volume of rice import. SAARC J. Agric., 22(2): 153-167 (2024)